Crossing the Threshold: Sojourning Together in the Wild Spaces of Love - Olthuis, James H. (Toronto journal of theology, 1995)
We live in a "time between times," a "place which is no place, " where, as Mark Taylor describes it, "sacred darkness lingers ... endlessly." Like it or not, the Enlightenment dream of a world increasingly controlled by the light of pure rationality is fading fast over the horizon. Control through reason and science has left wide swaths of destruction in its wake: systematic violence, marginalization, oppression, suffering, domination of the "other." It is that sorry history which both lies at the root of the postmodern attack on the totalizing power of reason, and gives shape to the postmodern ethical imperative to include the "other" and to make room for the "different." But what now, at the end of reason, after virtue, after philosophy, after God? What if there is neither a religion nor morality within the bounds of reason alone? Was Taylor right when he recently exclaimed: "[t]hough it continues, theology is as dead as the God for which theologians search,,? If the "sacred escapes the strictures of ontotheology,,,4 unattainable by either the via positive or the via negative, is the sacred beyond reach?